Occurrence of Endoparasites in Adult Swedish Dogs: A Coprological Investigation - Grandi, Giulio; Victorsson, Ida; Osterman-Lind, Eva; Höglund, Johan (Frontiers in Veterinary Science, 2021)
The occurrence of endoparasites in Swedish adult dogs (n=303) was investigated between January and October 2014. Included dogs had to be clinically healthy, older than one year and untreated with anthelmintics or endectocides for at least three months prior to sampling. They were grouped according to age, category of dog and time since last antiparasitic treatment. Samples were analyzed by flotation to detect parasitic eggs and cysts/oocysts. Among these, 129 (43%) dogs were also analyzed with the Baermann-technique to detect cardiopulmonary larval stages. Parasite dispersal stages were found in 24 (7.9%, CI 95% 4.9 - 10.1) of the dogs at flotation, while no dog shed cardiopulmonary larval stages. Giardia sp. cysts were observed in 2.6% (n=8) of dogs examined, cysts of Sarcocystis spp. were observed in 0.6% (n=2), oocysts of Cystosisopora ohioensis were found in one dog (0.3%). Eggs of Toxocara canis (2.3 %, n=7), Uncinaria stenocephala (1.3%, n=4) and Trichuris vulpis (0.3%, one dog) were found. None of the dogs were diagnosed with more than one species. Although the occurrence of endoparasites was above the average in dogs ≤2 years of age (11.5%), nematodes were more common in older dogs ≥4 years (77.0%). Although the occurrence was lower in working/exhibition dogs (5.9%) than in companion dogs (8.4%) and hunting-dogs (8.6%), these differences were not significant. However, dogs exposed to prey according to the owner had a statistically significant higher prevalence than other dogs (20.5% vs 5.7 %). The Odds Ratio (OR) was 4.0 (CI 95 %, 1.58 - 10.11) for dogs having access to prey, 2.4 (CI 95 %, 0.37 - 8.06) for dogs staying at day-care, and 2 (CI 95 %, 0.96 - 5.96) for bitches. Furthermore, a significant association was observed between infection with nematodes and exposures to prey (p=0.006). As a reference, data on the endoparasites in canine fecal samples submitted to the National Veterinary Institute (SVA, Uppsala) during 2014 are presented. Overall, this study shows a low occurrence of endoparasites among dogs in Sweden. Any risk-assessment on zoonotic parasites as well as deworming recommendations will take advantage from these updated figures.